A Paclitaxel Prodrug Activatable by Irradiation in a Hypoxic Microenvironment. Issue 51 (15th October 2020) - Zhou, Shiyu; Hu, Xiuli; Xia, Rui; Liu, Shi; Pei, Qing; Chen, Guang; Xie, Zhigang; Jing, Xiabin
Abstract: The innate hypoxic microenvironment of most solid tumors has a major influence on tumor growth, invasiveness, and distant metastasis. Here, a hypoxia‐activated self‐immolative prodrug of paclitaxel (PTX2 ‐Azo) was synthesized and encapsulated by a peptide copolymer decorated with the photosensitizer chlorin e6 (Ce6) to prepare light‐boosted PTX nanoparticle (Ce6/PTX2 ‐Azo NP). In this nanoparticle, PTX2 ‐Azo prevents premature drug leakage and realizes specific release in hypoxic tumor microenvironment and the photosensitizer Ce6 not only efficiently generates singlet oxygen under light irradiation but also acts as a positive amplifier to promote the release of PTX. The combination of photodynamic therapy (PDT) and chemotherapy results in excellent antitumor efficacy, demonstrating the great potential for synergistic cancer therapy. Abstract : A light‐boosted hypoxia‐activated self‐immolative paclitaxel prodrug nanosystem was designed for synergistic photodynamic therapy and chemotherapy. Upon irradiation, severe hypoxia occurred and amplified the specific release of paclitaxel from prodrug bridged with azobenzene. The nanoparticle showed superior antitumor efficacy with little toxicity to other organs.